Microeconometric Evaluation of the Active Labour Market Policy in Switzerland - Michael Lechner; Michael Gerfin (Institute for the Study of Labor (IZA), 2000)
In the second part of the 1990?s Switzerland conducted an ambitious active labour market policy (ALMP) encompassing a wide variety of programmes. We evaluate the effects of these programmes on the individual employment probability of potential participants. Our econometric analysis uses unusually informative data originating from administrative unemployment and social security records. We apply a matching estimator adapted for the case of multiple programmes. We find substantial positive effects for one particular programme that is a unique feature of the Swiss ALMP. It consists of a wage subsidy for temporary jobs in the regular labour market that would otherwise not be taken up by the unemployed. We also find large negative effects for traditional employment programmes operated in sheltered labour markets. For training courses the results are mixed.
Keywords: J64; C40; C14; H43; J68; 330; Unemployment; Swiss labour market; evaluation of multiple programmes; treatment; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Arbeitslosigkeit; Beschäftigungseffekt; Schätzung; Schweiz